International obligation in preventing trafficking in person: An examination of the anti- trafficking law in Tanzania - Mbalamwezi, Tausi (Mzumbe University, 2023)
A Dissertation submitted in Partial Fulfillment of the Requirement for the Award of Masters of Law (International Law) of Mzumbe University